Cholera in Pregnancy: A Systematic Review and Meta-Analysis of Fetal, Neonatal, and Maternal Mortality. - Nguyen-Toan Tran; Richard Taylor; Annick Antierens; Nelly Staderini (PLoS ONE, 2015)
Background Maternal infection with cholera may negatively affect pregnancy outcomes. The objective of this research is to systematically review the literature and determine the risk of fetal, neonatal and maternal death associated with cholera during pregnancy. Materials and methods Medline, Global Health Library, and Cochrane Library databases were searched using the key terms cholera and pregnancy for articles published in any language and at any time before August 2013 to quantitatively summarize estimates of fetal, maternal, and neonatal mortality. 95% confidence intervals (CIs) were calculated for each selected study. Random-effect non-linear logistic regression was used to calculate pooled rates and 95% CIs by time period. Studies from the recent period (1991-2013) were compared with studies from 1969-1990. Relative risk (RR) estimates and 95% CIs were obtained by comparing mortality of selected recent studies with published national normative data from the closest year. Results The meta-analysis included seven studies that together involved 737 pregnant women with cholera from six countries. The pooled fetal death rate for 4 studies during 1991-2013 was 7.9% (95% CIs 5.3-10.4), significantly lower than that of 3 studies from 1969-1990 (31.0%, 95% CIs 25.2-36.8). There was no difference in fetal death rate by trimester. The pooled neonatal death rate for 1991-2013 studies was 0.8% (95% CIs 0.0-1.6), and 6.4% (95% CIs 0.0-20.8) for 1969-1990. The pooled maternal death rate for 1991-2013 studies was 0.2% (95% CIs 0.0-0.7), and 5.0% (95% CIs 0.0-16.0) for 1969-1990. Compared with published national mortality estimates, the RR for fetal death of 5.8 (95% CIs 2.9-11.3) was calculated for Haiti (2013), 1.8 (95% CIs 0.3-10.4) for Senegal (2007), and 2.6 (95% CIs 0.5-14.9) for Peru (1991); there were no significant differences in the RR for neonatal or maternal death. Conclusion Results are limited by the inconsistencies found across included studies but suggest that maternal cholera is associated with adverse pregnancy outcomes, particularly fetal death. These findings can inform a research agenda on cholera in pregnancy and guidance for the timely management of pregnant women with cholera.